Accountability and Transparency through Water-Energy-Food Nexus Accounting in Central Asia - Siegfried, Tobias; Anarbekov, Oyture; Ragettli, Silvan; Marti, Beatrice (European Geosciences Union, 2023)
In Central Asia, more than 90 % of annually renewable water resources are consumptively utilized in irrigation, and allocation conflicts between large-scale hydropower in the upstream and irrigation in the downstream occur regularly and mostly across complex international borders, especially during water scarce years and low storage conditions. With increasing attention on climate-neutral hydropower solutions, including on small-scale hydropower. An abstract submitted to the EGU General Assembly 2022.